Efektivitas Metode Latihan Push-Up Terhadap Kecepatan Pukulan Jodan Zuki Pada Khensi Shorinji Kempo Dojo Universitas Negeri Gorontalo - Zulkifli Lamusu; Mohamad Reza Pratama Diuli; Sabri Sabri (Universitas Negeri Gorontalo, 2026)
This study aimed to determine the effectiveness of the push-up training method on the speed of the jodan zuki punch among Shorinji Kempo kenshi at the Gorontalo State University Dojo. The research employed a quantitative approach using an experimental method with a one-group pretest-posttest design. The sample consisted of 12 male kenshi selected through purposive sampling based on the criteria of being active practitioners and registered athletes. The research instruments included a handbox as the punching target and a stopwatch to measure the number of jodan zuki punches performed within 10 seconds. The push-up training program was conducted for six weeks with a frequency of three sessions per week, totaling 18 training sessions. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and hypothesis testing through the Paired Samples t-Test at a significance level of 0.05. The results showed that the mean speed of jodan zuki punches increased from 13.08 in the pre-test to 16.25 in the post-test, representing an improvement of 3.17 points or 24.24%. In addition, the standard deviation decreased from 2.81 to 2.52 and the variance decreased from 7.90 to 6.38, indicating greater homogeneity and consistency in athletes’ performance after completing the training program. The hypothesis testing results confirmed that the push-up training method had a significant effect on improving the speed of jodan zuki punches. Therefore, push-up training can be recommended as an effective, simple, and economical physical training method for enhancing punching performance in Shorinji Kempo athletes.